Immune system: Development and acquisition of immunological competence (2020)
Objectives: To describe the ontogeny ofthe immune system and the adaptive mechanisms ofthe immune system in the neonatal period, with an emphasis on transplacental antibody transport and breastfeeding. Source of data: Non-systematic literature review in the PubMed database. Summary of the findings: The last two decades have witnessed a great advance in the knowledge of the immune system since conception. Several investigation tools have provided insight on phenomena that were previously inadequately understood. Still expanding, the functional and molecular investigation of various aspects of the immune system will make it possible to understand how intra-uterus maternal-fetal exchanges, the maternal microbiota interacting with the fetus and newborn, and the acquisition of immunological competence occur in healthy and disease scenarios. Conclusions: In-depth knowledge of the development of the immune system and of the adaptive mechanisms that allow a safer transition to the extrauterine environment are fundamental components of optimizing maternal and young infant vaccination, as well as the strategies associated with full postnatal development, and the early diagnosis and treatment of innate errors of immunity